Punia Bhakti Rsi Yadnya: Implementasi Pengabdian Masyarakat Mendukung SDGs-2030 dan Asta Protas Kementerian Agama - Putu Gede Asnawa Dikta; Ni Luh Sinar Ayu Ratna Dewi; Ida Bagus Heri Juniawan; Ni Komang Wiasti; Ida Bagus Benny Surya Adi Pramana; Ketut Supartha (IAHN Gde Pudja Mataram, 2026)
This community service activity titled Punia Bhakti Rsi Yadnya was implemented by IAHN Gde Pudja Mataram on January 15, 2026, as part of the Siwaratri sacred day celebration. The activity aimed to manifest the Rsi Yadnya teaching, one of the Panca Yadnya in Hinduism, by paying homage to six Sulinggih (Hindu holy persons) in the Lombok region. The methods used include preparation, joint worship, group division, visits to Griya, presentation of parsel as Punia Bhakti, and receiving spiritual guidance. The results showed that 100% of the targets were achieved, with parsel successfully distributed to six Sulinggih and the strengthening of harmonious relations between higher education and Hindu religious figures. The satisfaction survey of 68 respondents indicated a very high satisfaction level, with 97.1% strongly agreeing that the theme aligns with Hindu values and 97.1% recommending this activity to the wider community. This activity contributed to achieving SDGs-2030 goals (Goal 1 and Goal 17) and supported the Asta Protas of the Ministry of Religious Affairs, particularly the pillars of Impactful Religious Services and Increasing Harmony and Love for Humanity.